Rapidly Shifting Concepts Regarding Androgens and Prostate Cancer - Abraham Morgentaler (The Scientific World Journal)
There has been a recent dramatic shift in our understanding of the relationship between androgens and prostate cancer (PCa). Whereas for several decades it had been assumed that higher serum testosterone (T) concentrations would lead to ever-greater PCa growth, current literature indicates that PCa growth is unaffected by changes in serum T throughout most of the naturally occurring range. A Saturation Model has been proposed to explain how prostate tissue can be exquisitely sensitive to changes in serum T at the very low end of the concentration range, but appears indifferent to such changes above the near-castrate range. This has special applicability to T-deficient men, since this means that T therapy may not be nearly as risky as once assumed. Indeed, one of the more interesting changes over the last several years has been the growing acceptance of the use of T therapy in men with a prior history of PCa, with early data indicating minimal risk of cancer recurrence or progression. Provocative new evidence suggests that it is not high serum T that is problematic for PCa, but low serum T that is associated with worrisome cancer features and outcomes, such as high Gleason score, advanced stage of presentation, and increased risk of biochemical recurrence after surgery. It will be interesting to see what changes will occur in this rapidly changing field over the next several years.